ASSOCIATION OF MOTOR DEVELOPMENTAL DELAY IN CHILDREN WITH AUTISM: A RETROSPECTIVE COHORT STUDY FROM A TERTIARY CARE CENTRE. - Krishna, Yallapragada Siva Rama; Vidya, Karasala Sri; Pavanchand, D.; Teja, Indla Ravi (Student's Journal of Health Research Africa, 2024)
Purpose For comparing children with autism spectrum disorder usually growing children's gross and fine motor profiles, this research was done. The study also evaluated whether the motor delay increased in severity with age. Methods This study compared children without autism spectrum disorders, the motor growth of those who usually develop, using data from children aged 12 to 60 months. The Schedule of Growing Skills II was utilized to evaluate their profile for growth. Utilizing statistical methods, the developmental profiles of the groups were examined. Results The study included a total of 50 children, comprising 29 children with autism spectrum disorder (ASD) and 21 typically developing (TD) children. Significant delays were observed in the ASD group, with 83.7% of these children exhibiting cognitive delays. Fine motor delays were present in 38.5% of children with ASD, and gross motor delays were noted in 6.7%. In contrast, none of the TD children exhibited such delays. The data further indicated that motor delays in children with ASD worsened with age, particularly in the older cohort (37-60 months), with 100% of gross motor delays and a higher percentage of fine motor delays in this age group. Statistical analysis using Fisher's exact test confirmed significant differences between the ASD and TD groups across all developmental domains assessed (p < 0.01). The findings highlight the necessity of early intervention to address motor delays in children with ASD, emphasizing the need for comprehensive developmental assessments. Conclusions Children suffering with ASD exhibit a discernible motor delay in contrast to children with normal development, and this delay only gets more severe as they grow older, making it imperative to assess their motor growth. Services for early intervention may be provided to maximize growth results in the event that motor delay is identified early.